Three-dimensional P-doped carbon skeleton with built-in Ni2P nanospheres as efficient polysulfides barrier for high-performance lithium-sulfur batteries. (1st June 2019) - Guang, Zhaoxu; Huang, Ying; Chen, Xuefang; Sun, Xu; Wang, Mingyue; Feng, Xuansheng; Chen, Chen; Liu, Xudong
Abstract: Rational design of modified separator is of great significance in effectively suppressing the shuttle of lithium polysulfides (LiPSs) and hence realizing fulfilling cycling performance of lithium-sulfur batteries (LSBs). In this paper, we developed a facile strategy to fabricate P-doped carbon coated CNT skeleton coupled with nickel phosphide (Ni2 P) nanospheres (PCCNT@NPS), and then we employed the as-developed hybrid as a multifunctional modified interlayer onto PP separator (denoted as PCNPmPP) to face the challenge of LiPSs shuttling. The as-prepared hybrid provides abundant physical confinement and strong chemical adsorption for inhibiting polysulfides shuttling as well as efficient catalysis for accelerating LiPSs converting. As a result, the LSBs based on PCCNT@NPS modified PP separator have delivered a highly reversible cycling performance with high initial discharge capacity of 1067 mAh g −1 and low capacity decay rate of 0.077% per cycle within 500 cycles at 1 C. The promising results demonstrate that the PCCNT@NPS composite is capable of effectively inhibiting the diffusion and shuttle of LiPSs. This paper provides a novel thinking for the synthesis of multifunctional interlayer onto PP separator for advanced LSBs.